2020
DOI: 10.3386/w27008
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perception Through the Lens of Politics in the Time of the COVID-19 Pandemic

Abstract: Zingales for helpful conversations, comments and suggestions. Jin Deng provided excellent research assistance. All errors are our own. We gratefully acknowledge the support of the Stigler Center and the Becker Friedman Center at the University of Chicago Booth School of Business. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

36
291
2
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(335 citation statements)
references
References 4 publications
36
291
2
6
Order By: Relevance
“…1 Gadarian et al (2020) present survey evidence showing partisan gaps in self-reported responses to the pandemic. Barrios and Hochberg (2020) show differences between Republican and Democratic areas in the frequency of COVID-related queries on Google and in movement patterns as measured in GPS data from a different source than the one we use. Painter and Qiu (2020) examine partisan heterogeneity in response to state-level, stay-at-home orders.…”
Section: Introductionmentioning
confidence: 85%
“…1 Gadarian et al (2020) present survey evidence showing partisan gaps in self-reported responses to the pandemic. Barrios and Hochberg (2020) show differences between Republican and Democratic areas in the frequency of COVID-related queries on Google and in movement patterns as measured in GPS data from a different source than the one we use. Painter and Qiu (2020) examine partisan heterogeneity in response to state-level, stay-at-home orders.…”
Section: Introductionmentioning
confidence: 85%
“…Related to our study is contemporaneous work studying correlations between political ideology and responses to the coronavirus. A number of studies find that areas with higher Republican vote shares practice less social distancing, as measured by cell phone GPS data (Allcott et al, 2020b; Barrios and Hochberg, 2020;Andersen, 2020;Wright et al, 2020). Allcott et al (2020b) additionally present survey evidence documenting substantial partisan differences in individual beliefs about personal risk and pandemic severity, while Barrios and Hochberg (2020) find that more Republican areas perceive lower risk, as measured by internet searches.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies find that areas with higher Republican vote shares practice less social distancing, as measured by cell phone GPS data (Allcott et al, 2020b; Barrios and Hochberg, 2020;Andersen, 2020;Wright et al, 2020). Allcott et al (2020b) additionally present survey evidence documenting substantial partisan differences in individual beliefs about personal risk and pandemic severity, while Barrios and Hochberg (2020) find that more Republican areas perceive lower risk, as measured by internet searches. Adolph et al (2020) show that both governors from states with more Trump supporters and Republican governors were slower to implement social distancing policies such as stay-at-home orders and school and business closures.…”
Section: Introductionmentioning
confidence: 99%
“…Jones, Philippon and Venkateswaran (2020), Barro, Ursua and Weng (2020), Eichenbaum, Rebelo and Trabandt (2020), and Kaplan, Moll and Violante (2020). Gormsen and Koijen (2020) Barrios and Hochberg (2020) and Allcott, Boxell, Conway, Gentzkow, Thaler and Yang (2020) show that political affiliations impact the social distancing response to the pandemic, and Coven and Gupta (2020) study disparities in COVID-19 infections and responses.…”
Section: Introductionmentioning
confidence: 99%